2006
DOI: 10.1186/1471-2105-7-55
|View full text |Cite
|
Sign up to set email alerts
|

PathSys: integrating molecular interaction graphs for systems biology

Abstract: Background: The goal of information integration in systems biology is to combine information from a number of databases and data sets, which are obtained from both high and low throughput experiments, under one data management scheme such that the cumulative information provides greater biological insight than is possible with individual information sources considered separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 42 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…al . data integrated (in A) ) into the IntegromeDB database and available to be analyzed in concert with wealth of other host-pathogen data available in BiologicalNetworks [ 40 - 42 ]. Host factors that were already present in our database and known to be related to viral response are colored green, whereas host factors newly discovered by Konig et.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…al . data integrated (in A) ) into the IntegromeDB database and available to be analyzed in concert with wealth of other host-pathogen data available in BiologicalNetworks [ 40 - 42 ]. Host factors that were already present in our database and known to be related to viral response are colored green, whereas host factors newly discovered by Konig et.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, the approach at cross-scale data integration to study host-pathogen interactions is proposed and demonstrated on a study of the Influenza infection. The proposed system is an extension of the previously developed BiologicalNetworks [ 40 , 41 ] and IntegromeDB [ 42 ]. It represents a general-purpose graph warehouse with its own data definition and query language, augmented with data types for biological entities.…”
Section: Introductionmentioning
confidence: 99%
“…Network models offer a powerful approach for the representation, integration, and analysis of the resulting data. Hence, the construction and analysis of genetic regulatory networks, 1 protein-protein interaction networks, metabolic networks, 2 and their combinations 3 , 4 are central concerns of systems biology. 1 10 Recent advances in systems biology have led to substantial progress on problems such as understanding the essential macromolecular sequence and structural features of molecular interactions; 11 extracting signaling pathways from gene and protein interaction networks; 12 , 13 discovering topological and other characteristics of these networks; 14 18 integration of disparate types of data (microarrays, proteomics, physical interaction, subcellular localization, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A number of tools are being developed for interpreting and exploring large-scale biological networks, such as: PathSys [8] , NAViGaTOR [9] , BIOZON [10] , [11] , BN++ [12] , ONDEX [13] , Cytoscape, and Osprey [14] . For a review of visualization tools for systems biology see [15] .…”
Section: Introductionmentioning
confidence: 99%